Single-Shot Anestesi Spinal Segmental Thoracic Atau Thoracic Spinal Anesthesia (TSA) Untuk Operasi Embolectomy Pada Pasien Dengan Acute Limb Ischemia (ALI) Stadium IIB : Laporan Kasus - Imam Ghozali; Tasrif Hamdi; Rizki Arisandi; Alda Putri Rahmadilla (Medula, 2022)
General anesthesia is the most widely used anesthetic and is the standard for most surgeries. However, general anesthesia has several disadvantages, including side effects of the drugs used, longer recovery time, and inadequate pain control. Therefore, the use of regional anesthesia is an alternative option to reduce the adverse effects of general anesthesia, one of which is spinal segmental thoracic anesthesia. In this case report, a 52-year-old woman that diagnosed with Stage IIb Acute Limb Ischemia (ALI) underwent embolectomy under thoracic spinal segmental anesthesia. The patient presented with ASA III physical status with type II DM, CHF, CAD3VD and increased coagulation factors. Thoracic spinal anesthesia with a paramedian approach at the level of the T10-11 vertebrae using a regimen of levobupivacaine 5 mg and bupivacaine 2.5 mg. The adjuvants used were dexmedetomidine 5 mcg, ketamine 15 mg, and fentanyl 25 mg. During the operation there were no hemodynamic fluctuations. Post-operative monitoring of the patient's condition was stable, pain control was good, and there were no complaints of headache, nausea, and vomiting. Segmental thoracic spinal anesthesia has several advantages such as the need for lower anesthetic doses, safer than lumbar spinal anesthesia, good pain control, faster recovery, and avoiding the side effects of general anesthesia. Therefore, this anesthetic technique can be an effective alternative choice for general anesthesia